Colonoscopy - Rex, Douglas K. (Endoscopy, 2013)
A large number of high-quality studies important to colonoscopy were presented at Digestive Disease Week (DDW) 2013, and the topics addressed by these studies reflect current controversies in colonoscopic practice. Thus, bowel preparation, quality measurements (particularly factors affecting adenoma detection), polypectomy technique, serrated polyps, real-time histology, and water immersion were covered in great detail. Studies covered here reflect the author’s perception of those providing new data or describing new approaches to current controversies in colonoscopy.